A secreted microRNA disrupts autophagy in distinct tissues of Caenorhabditis elegans upon ageing - Yifei Zhou (Nature Portfolio, 2019)
Decreased autophagy is a hallmark of ageing, but its inter-tissue regulation is poorly understood. Here, Zhou et al. identify mir-83 in C. elegans, which is transported across tissues and suppresses autophagy, contributing to age-related decline.